Seroprevalence of Measles-, Mumps-, and Rubella-Specific Antibodies in Future Healthcare Workers in Serbia: A Cross-Sectional Study - Ana Banko; Andja Cirkovic; Vladimir Petrovic; Mioljub Ristic; Vladimir Vukovic; Dobrila Stankovic-Djordjevic; Danijela Miljanovic (Vaccines)
Background/Objectives: Measles, mumps, and rubella (MMR) continue to pose a significant public health challenge due to insufficient immunization coverage. This study aimed to provide the first seroprevalence data against MMR and to explore self-reported immunity among future healthcare workers (HCWs) in Serbia, including women of childbearing age. Methods: We included 1296 future health care workers (HCWs) aged 19 to 29, born in Serbia. All HCWs supplied a blood sample for serology and filled in a questionnaire. Antibodies were measured using an enzyme immunoassay against measles, mumps, and rubella (MMR). Results: Anti-measles, -mumps, and -rubella seronegativity rates were 25.6%, 26.5%, and 4.4%, respectively, among future HCWs in Serbia. The mumps seronegativity rate was significantly higher in the oldest (27–29-year) age group, accompanied by significantly lower anti-mumps IgG GMCs in the same age group compared to younger participants (p = 0.035 and p < 0.001, respectively). Anti-mumps seronegativity also increased significantly across birth cohorts, from the youngest to the oldest (p = 0.004). Furthermore, anti-mumps IgG antibody GMCs were significantly higher among females, those who attended nursery/kindergarten, and unvaccinated individuals (p = 0.050, p = 0.020, and p = 0.005, respectively). Finally, older age and unvaccinated status were identified as independent factors associated with anti-measles and anti-mumps seronegativity among future HCWs in Serbia. Conclusions: The cross-sectional seroprevalence data revealed insufficient seroprotection in this population of particular importance, i.e., future HCWs, and women of childbearing age. These results strongly support the national recommendations for the mandatory vaccination of these populations. Identified immunity gaps should be closed promptly by strategic, targeted serologic screening, followed by vaccination of those lacking MMR antibodies.